Acceleration of polylactide degradation under biotic and abiotic conditions through utilization of a new, experimental, highly compatible additive. (August 2017) - Stloukal, Petr; Kucharczyk, Pavel
Abstract: This paper focuses on accelerating the biotic and abiotic degradation of polylactide by combining it with a newly developed experimental additive. Said additive is based on a highly carboxylic-functionalized poly(lactic acid) copolymer that possesses a comb-like architecture. Samples were prepared by melt blending, and analysis was carried out prior to degradation on changes in molecular weight and mechanical and rheological properties. Degradation studies were performed in compost and pH 7 water buffer environments. Such degradation was gauged by monitoring alteration in molecular weight, as well as in the content of carbon dissolved and CO2 evolved during composting. Furthermore, experimental data were treated by applying appropriate kinetic models. Results showed that the newly developed hydrolysis additive efficiently promoted biodegradation - even at a low dosage of 5% w/w, primarily due to reduction in the lag phase at the commencement of the process.